2002
DOI: 10.1136/gut.51.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Risk related surveillance following colorectal polypectomy

Abstract: Background: Patients who have had a colorectal adenoma are likely to develop a metachronous adenoma and therefore need to be kept under surveillance. It is essential to avoid unnecessary examinations by tailoring the frequency of follow up examinations to individual risk. Methods: A total of 3134 patients undergoing endoscopic removal of colorectal adenomas were prospectively recorded on the Erlangen Registry of Colorectal Polyps between 1978 and 1996. A multivariate analysis of 1159 patients on long term foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
2
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 37 publications
2
60
2
10
Order By: Relevance
“…We and others (5,26,27) have reported higher incidence of metachronous colorectal adenomas in patients with larger or more advanced colorectal lesions at the initial colonoscopy. A higher incidence of overall neoplasms from the subjects with more advanced lesions at the initial examination was also shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We and others (5,26,27) have reported higher incidence of metachronous colorectal adenomas in patients with larger or more advanced colorectal lesions at the initial colonoscopy. A higher incidence of overall neoplasms from the subjects with more advanced lesions at the initial examination was also shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CRC and adenomas are observed two to three times more frequently in males. Nusko et al (18) reported that 63.7% of patients with polyps were male. Similar to these results, 67.8% of patients with polyps in our study were male.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with polyps are male (25,26). Nusko et al (27) reported that 63.7% of the patients with polyps were male. In our study, 69.3% of the patients with polyps were male, and most polyps were found on the left side of the colon.…”
Section: Discussionmentioning
confidence: 99%